Structural rehabilitation of a Middle Byzantine ruin and the masonry building constructed above the ruin. Part I: The ruin. (November 2019) - Gunes, Baris; Cosgun, Turgay; Sayin, Baris; Ceylan, Oguz
Abstract: The objective of this study, which consists of a pair of articles, is the structural rehabilitation of a vaulted ruin located on the historical peninsula of Istanbul, dated to the Middle Byzantine period, and a masonry building constructed at a later date on top of the structure. The present article, which constitutes the first part of the study, examined the seismic performances of the historical ruin structure considering the states; (i) before the construction of the masonry building, (ii) after the construction of the masonry building and (iii) after the strengthening of the masonry building. Fieldwork and numerical analyses were conducted to this end. In this study, initially, the situations where the masonry building is present or not were compared, and the effects of the construction of masonry building on the seismic performance of the historical ruin structure are investigated. Then, the effect of the strengthening application on the masonry building to the historical ruin structure is revealed. For all of the three cases, the seismic strength of the historical ruin structure is found to be insufficient. The masonry building, which was built on the ruin in a later period caused a significant increase in the stresses and their distribution. A strengthening methodology to be applied to the historical ruin structure before the strengthening of the masonry building is proposed for the historical ruin structure to achieve its sufficient seismic strength. The findings of the study are significant in terms demonstrating the interaction between historical ruins and buildings constructed above them, and in defining the necessary strengthening applications required to achieve seismic safety in such structures. In addition, the primary motivation of the study is to present the necessary structural precautions needed for the preservation of ruins dated to the Middle Byzantine period through the structural analysis. Highlights: It is performed that seismic performance analyses of the ruin built in Middle Byzantine era. It is made a comparison of the historical ruin with and without the masonry building above to identify the effect of the later construction on the seismic performance of the historical ruin. A retrofitting proposal for the ruin is presented in order to achieve the sufficient seismic strength of the historical ruin.